Revolutionizing the Halal Food Industry: The Crucial Role of Green Halal Supply Chain in Pakistani Companies - A Compelling Theoretical Framework - Junejo, Safiullah; Anwar, Saba; Hamidi, M. Luthfi (Universitas Muhammadiyah Surakarta, 2023)
Food waste is a major environmental issue. Sustainable Halal food manufacturing reduces its environmental impact. This theoretical framework examines the pros and cons of greening Pakistani halal food. To maintain long-term profitability and market competitiveness, it stresses a Green Halal Supply Chain, a sustainable and environmentally responsible strategy. This framework shows how Pakistani enterprises may transform the halal food market by combining sustainability, halal certification, and supply chain management. Pakistan will benefit because other countries will accept Pakistani Halal standards as safe, clean, and environmentally friendly. Thus, the global Halal center relies on the green Halal supply chain. In response to these needs, the goals of this study are: first, to find out what green practices are used to manage the Halal food supply chain in collaboration with the supplier and customer; second, to find out what sustainable performance results from using green practices; and third, to find out if supplier-customer collaboration lessens the effect of green practices on sustainable performance. The goals of this study will be met through a mix of quantitative and qualitative methods. Overall, this study is supposed to develop a model that gives a complete picture of the Green Halal supply chain regarding how suppliers and customers work together to implement green practices. The model can help the business world and policymakers determine what green practices they can work together on and their pros and cons. Pakistan can build its reputation as the world's top Halal hub by joining the Green Halal supply chain.